Chemical and Mineralogical Analysis of Reformed Slag during Iron Recovery from Copper Slag in the Reduction Smelting - Urtnasan Erdenebold; Jei-Pil Wang Wang (Archives of Metallurgy and Materials, 2021)
Copper slag is usually a mixture of iron oxide and silicon dioxide, which exist in the form of fayalite (2FeO·SiO2), and contains ceramic components as the SiO2, Al2O3 and CaO depending on the initial ore quality and the furnace type. Our present study was focused on manufacture of foundry pig iron with Cu content from copper slag using high-temperature reduction smelting and investigate utilization of by-products as a reformed slag, which is giving additional value to the recycling in a replacement of raw material of Portland cement. Changes of the chemical and mineralogical composition of the reformed slag are highly dependent on the CaO concentration in the slag. The chemical and mineralogical properties and microstructural analysis of the reformed slag samples were determined through X-ray Fluorescence spectroscopy, X-Ray diffractometer and Scanning Electron Microscopy connected to the dispersive spectrometer studies.